2017
DOI: 10.3906/zoo-1510-15
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of soft bottom polychaetes of Sinop Peninsula(southern Black Sea) with new records

Abstract: IntroductionPolychaeta is one of the most diverse and abundant benthic groups in marine ecosystems: 12,632 species of polychaetes are reported in the world's oceans (Appeltans et al., 2012), while 1122 species are reported in the Mediterranean Sea (Coll et al., 2010) and 238 species in the Black Sea to date (Kurt Şahin and Çınar, 2012). The polychaetes distributed among the Turkish coasts were recently reported by Çınar et al. (2014) with 459 species from the coast of the Levantine Sea, 547 species from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the Mediterranean also known from France (Blake et al 2009) and Turkey (Çınar et al 2017). Present in the adjacent Sea of Marmara (Çinar et al 2015) and Black Sea (Kurt-Şahin et al 2017). Otherwise distributed in the North Atlantic and Pacific Ocean.…”
Section: Checklistsmentioning
confidence: 99%
“…In the Mediterranean also known from France (Blake et al 2009) and Turkey (Çınar et al 2017). Present in the adjacent Sea of Marmara (Çinar et al 2015) and Black Sea (Kurt-Şahin et al 2017). Otherwise distributed in the North Atlantic and Pacific Ocean.…”
Section: Checklistsmentioning
confidence: 99%
“…Protodorvillea egena (Ehlers, 1913) was reported from the Mediterranean (Zenetos et al 2005(Zenetos et al , 2010Coll et al 2010;Occhipinti-Ambrogi et al 2011;Cinar 2013) and first recorded along the Italian coasts, from Sicily (Cantone 2001), likely introduced through the Suez Canal as lessepsian migrant (Amoureux 1983). Protodorvillea kefersteini (McIntosh, 1869) is widely distributed from the North Atlantic to the North Sea and English Channel (Pettibone 1961;Jumars 1974;Perkins 1979;Hartmann-Schröder 1996), Mediterranean (Coll et al 2010;Núñez et al 2013;Çinar et al 2015;Mikac 2015) and the Black Sea (Jakubova 1930;Kurt Sahin et al 2017); P. atlantica was reported from Greece by Vamvakopoulou (1991), although Faulwetter et al (2017) suggested that this record must be considered questionable; in the Mediterranean this species is also known from Tunisia (Zaâbi et al 2009) and the Adriatic Sea (Mikac 2015). Protodorvillea atlantica was firstly described by McIntosh (1885) as Staurocephalus atlanticus, and reported from the Atlantic Ocean by Fauvel (1923).…”
Section: Introductionmentioning
confidence: 99%